2022
DOI: 10.1111/cdev.13744
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐racism activism among Black adolescents and emerging adults: Understanding the roles of racism and anticipatory racism‐related stress

Abstract: This study examines associations between individual racism, anticipatory racism-related stress, and anti-racism activism among Black adolescents (n = 443; M age = 15.6; 57.4% female) and emerging adults (n = 447; M age = 23.8; 77.6% female).The authors tested competing hypotheses about associations between individual racism and anti-racism activism on anticipatory racism-related stress. Findings indicated anticipatory racism-related stress may be both a catalyst and consequence of engagement in anti-racism act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Individuals facing the adaptive problem of racial discrimination tend to employ a variety of coping strategies, including critical consciousness/action behavior (Hope et al, 2020;Roy et al, 2019). Among Black adolescents and emerging adults, for example, more stressful experiences of racial discrimination are associated with more antiracism activism, such as confronting others who make racist comments, strong support for Black Lives Matter, and participating in protests and demonstrations (Hope et al, 2022). In turn, critical consciousness/action behavior, in and of itself, may promote ecologically relevant skills that support positive youth development.…”
Section: Racial Discrimination Critical Consciousness and Development...mentioning
confidence: 99%
“…Individuals facing the adaptive problem of racial discrimination tend to employ a variety of coping strategies, including critical consciousness/action behavior (Hope et al, 2020;Roy et al, 2019). Among Black adolescents and emerging adults, for example, more stressful experiences of racial discrimination are associated with more antiracism activism, such as confronting others who make racist comments, strong support for Black Lives Matter, and participating in protests and demonstrations (Hope et al, 2022). In turn, critical consciousness/action behavior, in and of itself, may promote ecologically relevant skills that support positive youth development.…”
Section: Racial Discrimination Critical Consciousness and Development...mentioning
confidence: 99%
“…Moreover, in this growing body of research, there has not been a thorough examination of the potential for developmental stage to shape associations between experiencing racism‐related stress and anti‐racist activism. Seeking to address these gaps, Hope and colleagues (2022) tested competing models to examine two critical questions: (1) Is anti‐racism activism a reaction to racial stress? (2) Does anti‐racism activism potentially cause racial stress?…”
Section: Overview Of Special Section Articlesmentioning
confidence: 99%
“…In particular, a study [27] found that cultural socialization decreased substance use via stronger social bonds. Hence, it is likely that those who grew up socialized with messages of racial and cultural pride may be more socially resilient in seeking online social support and advocating for racial justice [28] in response to online racism and engage in less risky coping strategies such as alcohol use.…”
Section: Coping With Online Racism and Ethnic-racial Socializationmentioning
confidence: 99%
“…First, at the individual level, clinicians working with racial/ethnic minority individuals experiencing online racial violence should consider how their clients have been socialized to deal with racism and their resulting tendency to engage in or disengage from online social support seeking. In particular, clinicians must be aware of the health risks involved with disengagement tendencies and help them begin to consider affirmation strategies to deal with online racism, and eventually promote the development of a network of support and counterspaces to externalize the deficits linked to online racism [28,53]. Clinicians must also be aware that those who actively engage in online social support seeking and advocacy at high levels may seemingly appear to be dealing with online racism, but they may be engaging in self-medicative alcohol use to cope with the psychological toll of sustaining such process.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation